Wireless Intelligent Power Switch berbasis Wireless Sensor Network - Ridho Hendra Yoga Perdana; Amalia Eka Rakhmania; Aad Hariyadi (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2020)
Increasing demand for electricity also implies a rise in conventional energy use, and by using conventional energy, leading to disadvantages such as being environmentally unfriendly as a result of fossil fuel use. The system to be researched is a wireless intelligent power switch. The system will be created using 2 types of resources and each load will be linked to a switch to determine the power distribution. The power distribution decision making involves an artificial intelligence-based on backpropagation neural network. The results of the comparison between the outcomes of Matlab simulation and the anticipated target showed excellent outcomes after testing the system, with accurate 94.3% and delay transmission 5 – 10 second.